Systematic Literature Review: Peran Infrastruktur Logistik dalam Mendukung Pertumbuhan Ekonomi Daerah Terpencil di Indonesia - Maharani Rahayu; Dwi Novi Wulansari (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
High logistics costs are a major challenge in Indonesia, particularly in remote areas such as Papua, due to limited infrastructure and transportation access. This study aims to analyze the role of logistics infrastructure in reducing logistics costs and supporting economic growth using a systematic literature review method. The results show that the development of toll roads, ports, the Sea Toll program, and multimodal transportation can improve connectivity, reduce price disparities, and facilitate the distribution of goods. Logistics infrastructure also creates economic opportunities, attracts investment, and improves community welfare. Therefore, the development of sustainable logistics infrastructure is crucial for supporting equitable development and national economic growth.